Strategic Literacy Management through the POAC Model: Strengthening the Gerakan Literasi Sekolah in Indonesian Primary Education - Riscky Risgianti; Agus Mulyanto (Journal of Science and Education (JSE), 2025)
This study investigates the management of poetry-writing literacy programs in elementary schools through the application of the POAC (Planning, Organizing, Actuating, and Controlling) management model within the framework of the Gerakan Literasi Sekolah (GLS) and the Kurikulum Merdeka. Employing a qualitative multi-site case study design, the research was conducted at SDN Jambudipa 1 and SDN Cimanggu in Cianjur, West Java. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that effective program management characterized by systematic planning, participatory organization, creative implementation, and adaptive evaluation significantly enhances students’ interest, creativity, and performance in poetry writing. Quantitative data show an increase of 42–57% in students’ interest levels, while the average number of poems produced more than doubled, and rubric-based scores improved from 68–70 to 82–85. Qualitative evidence further demonstrates growing learner autonomy, motivation, and engagement as students began to express local culture, nature, and personal reflections through poetry. These results underscore that when GLS and Kurikulum Merdeka are operationalized through structured managerial frameworks, they yield transformative educational impacts beyond linguistic skills strengthening character formation, critical thinking, and aesthetic appreciation in alignment with the values of the Profil Pelajar Pancasila. The study concludes that integrating systematic management practices with culturally grounded pedagogy is essential for ensuring the sustainability and contextual relevance of school-based literacy programs.